2015
DOI: 10.1016/j.nut.2015.05.023
|View full text |Cite
|
Sign up to set email alerts
|

Dietary fats significantly influence the survival of penumbral neurons in a rat model of chronic ischemic by modifying lipid mediators, inflammatory biomarkers, NOS production, and redox-dependent apoptotic signals

Abstract: Dietary lipids modulate NOS and PLA2 activities, ceramide production, and glutathione import into the mitochondrial matrix, finally determining the activation of the two main protease systems involved in programmed cell death. Olive oil appears to be a biological source for the isolation of protective agents that block the expansion of brain core at the expense of penumbral neurons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2016
2016
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 79 publications
0
6
0
1
Order By: Relevance
“…We consider that the composition of dietary fat may influence and modulate the outcome of stroke and the patient’s subsequent evolution by regulating antioxidant and anti-inflammatories activities. Olive oil has antioxidant and neuroprotective properties [52], and recent studies demonstrated the positive properties of DHA treatment after MCAo in rat stroke models, producing a reduction in infarct volume and edema, and an improvement in the neurological deficits due to the activation of NPD1 synthesis [53,54]. Furthermore, DHA reduces apoptosis in the brain by stimulating antiapoptotic processes, dampening responses to ROS, downregulating the expression of proapoptotic proteins, upregulating the expression of antiapoptotic proteins, and preserving mitochondrial function and integrity [55].…”
Section: Discussionmentioning
confidence: 99%
“…We consider that the composition of dietary fat may influence and modulate the outcome of stroke and the patient’s subsequent evolution by regulating antioxidant and anti-inflammatories activities. Olive oil has antioxidant and neuroprotective properties [52], and recent studies demonstrated the positive properties of DHA treatment after MCAo in rat stroke models, producing a reduction in infarct volume and edema, and an improvement in the neurological deficits due to the activation of NPD1 synthesis [53,54]. Furthermore, DHA reduces apoptosis in the brain by stimulating antiapoptotic processes, dampening responses to ROS, downregulating the expression of proapoptotic proteins, upregulating the expression of antiapoptotic proteins, and preserving mitochondrial function and integrity [55].…”
Section: Discussionmentioning
confidence: 99%
“…Olive oil diet was protective in terms of redox homeostatic balance, minor increases in lipid and protein damage, protective activation of nitric oxide synthase (NOS) in penumbra neurons, and apoptosis (caspase-3, milli- and microcalpains). 52 In another study, male Wistar rats were fed for 60 days on the same basal diet plus olive oil or grape seed oil, and the lipid FA composition of liver, enzymatic and nonenzymatic components of the antioxidant defense system, and the activity of enzymes involved in lipid metabolism were evaluated. The grape seed oil group showed significantly increased oxidative stress biomarkers, and the enzymatic and nonenzymatic components of the antioxidant defense system were increased in the olive oil group.…”
Section: Grape Seed Oil and Translationmentioning
confidence: 99%
“…The PREDIMED trial, which studies the effect of Mediterranean diets in health, has highlighted the positive association between extra-virgin olive oil (EVOO) consumption and the risk of stroke in humans [10,11]. This beneficial effect of EVOO has also been shown to be protective in terms of redox homeostatic balance, lipid and protein damage, activation of NO synthase (NOS) in the penumbra, and reduction of apoptosis levels in chronic ischemic models [12,13,14].…”
Section: Introductionmentioning
confidence: 99%